Leadership’s Role in Overcoming Ethical Challenges: Implementing Islamic Business Ethics in the Palm Oil Industry - Raihan, Raihan; M. Ambia, M. Ambia (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
This study investigates the role of leadership in implementing Islamic business ethics at TBS Kelapa Sawit Mega Lestari, focusing on identifying challenges and strategies to overcome them. A qualitative descriptive approach was employed, involving direct observations, semi-structured interviews with 10 key informants (comprising company leaders, field employees, and local farmers), and an analysis of documentation. Findings indicate that the successful implementation of Islamic business ethics—centered on fairness, honesty, transparency, and social responsibility—is heavily dependent on the leadership's ability to educate employees and establish ethically aligned partnerships. Key challenges identified include employees’ limited understanding of Islamic ethical principles and inconsistencies with partner companies not adhering to these values. To address these, the leadership implemented Focus Group Discussions (FGDs) conducted quarterly to enhance awareness and introduced measures to collaborate with partners fully aligned with Islamic ethics. This study concludes that while notable progress has been made, continuous efforts are required to standardize ethical practices and foster a culture aligned with Islamic principles within the palm oil industry.